How do mindfulness-based interventions promote coping and self-efficacy in patients with cancer: A systematic review of qualitative and quantitative data - Heinen, Jana Maria; Laing, Ebba Magdalena; Schäffeler, Norbert; Bäuerle, Alexander; Krakowczyk, Julia Barbara; Schug, Caterina; Ziesemer, Stefanie Katharina; Teufel, Martin; Erim, Yesim; Zipfel, Stephan; Stengel, Andreas; Graf, Johanna (Psycho-Oncology, 2024)
Objective: The purpose of this study was to review the existing quantitative and qualitative evidence regarding how mindfulness-based interventions (MBIs) help cope with cancer-related challenges and increase affected patients' perceived self-efficacy. Methods: A systematic literature search was conducted on PubMed, PsycInfo, PubPsych, and CINAHL. Quantitative, qualitative, and mixed methods studies were included if they (1) evaluated MBIs (2) for patients with cancer or cancer survivors (3) regarding their impact on coping with cancer and perceived self-efficacy. The reports were screened by two independent reviewers and conflicts were resolved by a third reviewer. The review was pre-registered on PROSPERO (CRD42022368765). Results: Findings from 28 reports of 19 quantitative studies, six qualitative studies, and three mixed-methods studies (total N = 1722) were extracted and integrated. The synthesis of quantitative data showed considerable heterogeneity in outcomes and measurement instruments. Most often reported were significant positive impacts of mindfulness on general coping skills, self-regulation, and perceived efficacy in coping with cancer. Qualitative interviews with patients supported those results. The three meta-themes identified were that MBI (1) provided patients with tools to use in stressful situations, (2) promoted a general change of mindset and (3) created a feeling of social connectedness. Conclusions: The reviewed studies suggest that MBI can promote coping and enhance the perceived self-efficacy of patients with cancer. In the future, more research investigating the different aspects of coping and the potentially moderating role of self-efficacy could provide further insights with respect to how coping and self-efficacy related to MBI.
CRIS-Team Scopus Importer:2024-05-31
Keywords: cancer; coping efficacy; coping with cancer; mindful coping; mindfulness-based cancer recovery; mindfulness-based intervention; mindfulness-based stress reduction; oncology